Provenance and tectonic significance of the Cenozoic sandstones in Sabah: Constraints from zircon geochronology and Lu-Hf isotope - Wei Pingting; Qian Xin; Junaidi Bin Asis; Wang Yuejun (Geotectonica et Metallogenia, 2024)
Sabah in Borneo is located in the junction region of the Indo-Australian, Pacific, and Philippine Sea plates, and experienced complex tectonic evolution. The Cenozoic sedimentary strata in Sabah preserved important fingerprints for understanding the sedimentary-tectonic evolution of Northern Borneo. This paper presents petrographic and detrital zircon U-Pb geochronological results, as well as zircon in-situ trace elemental and Lu-Hf isotopic results for the Eocene Miocene sandstones in Northern Sabah. These results indicate that the sandstones are characterized by lithic quartz sandstone and feldspar lithic quartz sandstone. Detrital zircons from the Eocene Trusmadi Formation show two main age peaks at ca. 160 Ma and ca. 120 Ma, with εHf(t=185–145 Ma and 140–100 Ma) ranging from –15.6 to +14.8 and +0.6 to +12.2, indicative of significant juvenile crustal materials in the provenance. The detrital zircon from the Eocene-Miocene Crocker Formation has a main peak at ca. 248 Ma and four secondary age peaks at ca. 1860 Ma, ca. 438 Ma, ca. 280 Ma, and ca. 120 Ma, and the corresponding εHf(t=265–220 Ma) values range from –11.9 to +9.9. Detrital zircon apparent ages for the Miocene Kudat Formation yielded a major age peak of ca. 120 Ma and a secondary age-peak of ca. 174 Ma, with positive εHf(t=140–100 Ma) values of +1.8–+9.0, indicating that juvenile crustal materials were the main contributor to the provenance. Our results indicate that the Trusmadi sandstone was sourced from Mesozoic intermediate-acid igneous rocks in the Vietnam Dalat Zone and Western Borneo and recycled sediments from the Sarawak Kuching zone. The Crocker sandstones are mainly Mesozoic igneous rocks from Western Borneo and East Malaya, along with associated rocks from Sabah. The Kudat sandstones were mainly from the Sabah ophiolitic mélange and partially recycled sediments from the Palawan continental terrane. Our results also suggest the existence of Eocene magmatism associated with subduction of the Proto-South China Sea in Sabah.